From Conventional to Innovative Approaches for Pain Treatment - Cascella, Marco (IntechOpen, 2019)
Although there have been notable advances in pain medicine in recent decades, pain relief often remains an unmet need in both acute and primary or secondary chronic painful conditions. This poses a great challenge because pain as a symptom and pain as a disease are leading causes of suffering and disability. This book analyzes several important aspects of pain treatment, from acute pain in surgical settings to chronic pain in cancer and other diseases, from opioids research to interventional procedures, and from optimization of conventional strategies to innovative therapeutic approaches. Coverage of these topics is augmented with attractive iconography and up-to-date references. This volume is an important source for specialized pain therapists, owing to the comprehensive coverage of the topics and the scientific value of each chapter. Furthermore, for nonspecialized physicians, it is a very useful guide for managing different types of pain.